KARAKTERISASI BEBERAPA STRAIN GURAMI Osphronemus gouramy Lac. MENGGUNAKAN MARKA RAPD - Anisa Kartika Sari; Agus Nuryanto; Agus Hery Susanto (Fakultas Biologi | Universitas Jenderal Soedirman, 2014)
Giant gouramy, Osphronemus gouramy Lac. is a popular fish species in Indonesia, especially in Java and Sumatera as this freshwater fish species has a high economic value of stable price. Fish farmers in Bogor divide giant gouramy into six strains based on egg productivity, growth rate, and maximum weight of the adult. They are soang, jepang, blue saphire, paris, bastar, and porselin. These various strains lead to the need of study on the genetic relationship among them, which can be performed by the use of RAPD (Random Amplified Polymorphic DNA) marker. This study aims to determine primers producing consistent and polymorphic RAPD markers, determine specific RAPD markers, and know the genetic relationship among several giant gouramy strains. The strains used in this study are soang, jepang, and blue saphire. Survey method was applied employing purposive random sampling technique. Total genomic DNA was isolated using Genjettm genomic DNA purification kit (Fermentas), which was then used as template to amplify RAPD markers with primers OPA-07, OPA-09, OPA-11, OPA-20, OPAH-01, OPAH-08, OPAH-09, and OPAC-14. The variables examined were patterns and numbers of specific DNA fragments as the PCR amplification products. Selected primers were determined descriptively on the basis of specific DNA bands appearing on the agarose gel. Genetic diversity was predetermined by changing qualitative band pattern into quantitative binnary data. Genetic relationship was analyzed using cladistic method with PAUP software. The results showed that only five of the eight primers produce consistent and polymorphic RAPD markers, i.e. OPA-11, OPA-20, OPAH-1, OPAH-8, and OPAH-9. Specific RAPD markers which can be used to distinguish several gouramy strains are those amplified with OPA-20 of 786 bp, OPA-20 of 1,176 bp, OPAH-8 of 1,000 bp and OPAC-14 of 1,607 bp. Nervertheless, it was found that RAPD markers cannot be used to clearly determine genetic relationship among gouramy strains.